Digital Comics as Learning Media to Improve Students’ Vocabulary Mastery - Farissi, Fatchurachman Al; Ahsanu, Muhamad; Kariadi, Mustasyfa Thabib (JELLE, 2024)
Digital comics as learning media are greatly required for students’ vocabulary mastery. The purposes of this research are: (1) to figure out the implementation of digital comics used as learning media for students’ vocabulary mastery; (2) to find out the significant effect of digital comics used as learning media on students’ vocabulary mastery and (3) to investigate the students’ perception on the digital comics as learning media for students’ vocabulary mastery. This research used a quantitative method with a quasi-experiment design. The participants involved in this study were Grade VIII students at SMP Negeri 2 Patikraja. The samples were purposively selected using certain criteria. The data were collected using tests, questionnaire, and observation check-list. The data were then analyzed using independent t-test. The result showed that digital comics was successfully implemented supported by the students’ activities such as reading comics, understanding story, finding words, translating words, and presenting the work. Digital comics as learning Media significantly influenced the students’ vocabulary mastery supported by the significance value of 0.000 (0.000 < 0.05). Students also argued that digital comics gave positive effects supported by the students’ total response percentage of 96.2%. The conclusion showed that digital comics positively and significantly influenced the students’ vocabulary mastery. Keywords: Digital Comics, Learning Media, Vocabulary Mastery